Relative position of mandibular foramen in 4-9-year-old children: A retrospective study - Sruthi Chandran; Faizal C Peedikayil; T P Chandru; Soni Kottayi; Seena John (Wolters Kluwer Medknow Publications, 2021)
Introduction: Most common nerve block used in children is the inferior alveolar nerve block (IANB) for anesthetizing mandibular teeth. Therefore, knowledge of the location of the mandibular foramen is necessary for a successful IANB anesthesia. Aim: The study aimed to correlate the position of mandibular foramen in relation to the mandibular occlusal plane and the deepest point of the coronoid notch as a clinical guide for IANB injection in 4-9-year-old children. Materials and Methods: One-hundred orthopantamographs were analyzed and divided into two groups; Group 1 (4-6 years) and Group 2 (7-9 years). The orthopantamographs were traced on the acetate paper using a radiograph viewer and measurements were taken from mandibular lingula (ML) to the occlusal plane and to the deepest point of the coronoid notch. Results: Statistical analysis of the data revealed that there was a significant difference in mean distance between the two groups on both sides by measuring the position of ML to the mandibular occlusal plane and to the deepest point of the coronoid notch. Intergroup comparison of the distance from ML to the deepest point of the coronoid notch on the right and left sides shows a statistically significant difference (P < 0.001). Conclusion: There is a significant difference in both the distance and position of mandibular foramen in the considered age groups.